2019
DOI: 10.31728/jnn.2019.00050
|View full text |Cite
|
Sign up to set email alerts
|

Middle Cerebral Artery Pulsatility Is Highly Associated with Systemic Blood Viscosity in Acute Ischemic Stroke within 24 Hours of Symptom Onset

Abstract: Background: Though blood viscosity (BV) is the major factor influencing pulsatility index (PI), it is unknown whether PI is related with BV in acute ischemic stroke. We explored the association between transcranial Doppler (TCD) PI and BV in acute ischemic stroke patient. Methods: Between January 2018 and December 2018, patients aged 40 years or older with an ischemic stroke or transient ischemic attack within 24 hours of symptom onset were recruited for the study. The scanning capillary-tube viscometer was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…We previously reported that middle cerebral artery (MCA) pulsatility is highly associated with systemic blood viscosity (BV) in acute ischemic stroke within 24 hours of symptom onset. 1 Our findings indicated that transcranial Doppler (TCD) pulsatility index (PI) is a useful non-invasive imaging modality for exploring the viscosity of cerebral vessels. We also showed that prior antithrombotic use was significantly associated with decreased BV in acute ischemic stroke patients.…”
Section: Ntroductionmentioning
confidence: 87%
See 1 more Smart Citation
“…We previously reported that middle cerebral artery (MCA) pulsatility is highly associated with systemic blood viscosity (BV) in acute ischemic stroke within 24 hours of symptom onset. 1 Our findings indicated that transcranial Doppler (TCD) pulsatility index (PI) is a useful non-invasive imaging modality for exploring the viscosity of cerebral vessels. We also showed that prior antithrombotic use was significantly associated with decreased BV in acute ischemic stroke patients.…”
Section: Ntroductionmentioning
confidence: 87%
“…BV is uniform over a short period of time and TCD PI is influenced by several physiological factors. 1 One study demonstrates that BV at admission is significantly higher in patients with lacunar stroke but drops after 2 weeks of normal hydration. 3 Our previous study also shows that PIs decreased in the first 14 days after the lacunar stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the use of TCD as a screening tool for high ICP when deciding on operating, placing an ICP catheter or shunting 18,23 seems to be more reliable than using TCD as a surrogate technique after these procedures 24,25 . Furthermore, when interpreting the PI in the setting of acute brain injuries one should take into account that other factors may increase the PI, as aging 26 , diabetes 27 , arterial hypertension 28 , sepsis 29 , dehydration and blood viscosity 30 , oxygenation 31 and sedatives as barbiturates 32 for example. Thus, PI elevation may be a better indicator of some degree of CPP reduction than a surrogate marker for IH 33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…A specify measurement to point out the relationship between stroke and BV is essential. The artery pulsatility is highly associated with blood viscosity in acute ischemic stroke within 24 hours of symptom onset (Han et al, 2019). An appropriate physical measurement model to evaluate the stroke happening risk is observing the viscosity of non-Newtonian property of blood by different shear rate conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement model of the parallel laminar ow is a powerful method for accuracy and precision viscosity detection. Here we used speci c microgeometry to create the blood viscosity measurements with artery pulsatility ow which are simulated by systolic blood viscosity (SBV) and diastolic blood viscosity (DBV) (Han et al, 2019). That provide the in-vitro evaluation system to observing the variable of blood viscosity, one of shear rate conditions, in particular vessel wall for stroke risk factor.…”
Section: Introductionmentioning
confidence: 99%